VHDL design and FPGA implementation of direct torque control for induction machines - Elhabib Lotfi; Mustapha Elharoussi; Elhassane Abdelmounim (Institute of Advanced Engineering and Science, 2021)
This paper presents a VHDL design and an FPGA implementation of a direct torque controller (DTC) used to order induction machines (IM). The use of FPGA at high sampling frequency reduces the torque ripple while maintaining the classical DTC control structure. We have adopted a modular approach, by dividing the global entity into a set of elementary blocks designed and implemented separately. The performances of this command are to reduce the torque ripple to 0.01 Nm and the flux ripple to 0.01 wb with a circuit implementing DTC control of 3,256 LEs of complexity and 64 latency clock cycles. To evaluate the performance of our FPGA circuit implementing DTC controller, we have performed a co-simulation platform based on MATLAB/Simulink and Modelsim programs. MATLAB/Simulink was used to simulate the dynamics of the induction machine associated with its inverter and the proposed DTC control strategy was executed under the modelsim software using the VHDL fixed point. We have operated our circuit FPGA in the loop in a speed variation platform of induction machine and we have obtained the following performances: A zero overrun, response time at speeds of 300 ms and a zero static error as required in the specifications.